Parkinson's disease - Landau, Elaine (New York : F. Watts, 1999)
Introduces Parkinson's disease, a nerve disorder that often causes uncontrollable shaking and loss of energy in its victims.
Includes bibliographical references (p. 97-98) and index.
Keywords: Parkinson's disease -- Juvenile literature; Parkinson's disease; Diseases